CREATING EDUCATIONAL VIDEOS IN THE PROCESS OF STUDENTS’ PROJECT ACTIVITY - Halyna Khrapiichuk; Nataliia Stuchynska; Ihor Prokhorenko (Неперервна професійна освіта: теорія та практика)
This article explores the role of digital visualizations in fostering motivation among students of medical (pharmaceutical) higher education institutions to study physical and mathematical disciplines. The main focus is on creating dynamic visualizations that simulate physical and biophysical phenomena and processes occurring within the human body. Based on an analysis of scientific sources, surveys, and observations, it is concluded that the use of dynamic visualizations can become an effective and useful tool for developing the professional competence of future healthcare professionals. The aim of the article is to substantiate methodological foundations for creating explainer videos within student project work in medical and biological physics. Research methods include: theoretical methods – collection and systematization of scientific and methodological literature, analysis, synthesis, and generalization; empirical methods – conversations and surveys in focus groups, student project activities, and assessment of students’ academic achievements. The possibilities of applying dynamic visualizations in group and individual projects of higher medical education students are examined. A new format for student project work is proposed: the creation of explainer videos and motion visualizations that illustrate biophysical phenomena and processes important for the professional development of future doctors. An essential requirement is the use of only scientifically validated materials from peer-reviewed sources. This approach promotes critical thinking, the formation of academic culture, and the ability to analyze information from various sources. It is shown that the use of digital learning tools can significantly enhance awareness and understanding of the physical nature of the main processes occurring within the human organism. Presenting complex processes visually through digital visualization methods simplifies the perception of abstract concepts, engages students’ attention, accelerates the acquisition of knowledge in fundamental natural sciences, and contributes to the development of digital and medical-clinical competencies of future healthcare professionals. Teachers collaborating with students also master new software products and improve their digital literacy. The created collection of digital visualizations can be viewed as an innovative educational resource that meets the needs of modern didactics and the preferences of young people.